Potassium Derived from Molasses (PDM)–A Potassium-Rich Nutrient Gold for Agriculture - Gobinath, R.; Vijayakumar, S.; Manasa, V.; Basavaraj, K.; Jesudas, G.; Suvana, S.; Kumaresan, P. (Chronicle of Bioresource Management, 2025)
Molasses, a byproduct of sugar extraction from sugarcane, contains various minerals, including potassium. When molasses is processed, it can be used to produce potassium fertilizers. The extraction process involves dissolving molasses, isolating potassium through chemical reactions, and purifying it to meet agricultural standards. This potassium can then be formulated into fertilizers suitable for various crops. Potassium derived from molasses (PDM) is used as an alternate supplement to synthetic chemical fertilizer for potassium nutrients and the use of PDM will not degrade the environment and enrich the soil with organic inputs. Because of it’s organic origin, PDM could be inducted into a package of practices in organic farming to sustain soil health in the long run. This approach improves soil health, increases crop yields, and supports environmentally conscious farming practices.